Perancangan Aplikasi Ujian Online Berbasis Website - Fritz Gamaliel; P. Yudi Dwi Arliyanto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
The online exam information system is one part of the distance education system through internet technology media. Colleges use Moodle as an online application for new student admissions, in this case Moodle is not integrated with the College's internal system. The concept of an online exam that is not limited by space and time can be a solution to the obstacles that exist in conventional exam methods. The process of collecting data using the method of observation, interviews and literature study. In system development using the Extreme Programming method. System design tools used are Class diagrams, and Use case diagrams. Meanwhile, to create an online exam information system at the university, the author uses the PHP programming language and MySQL database. Based on the results of the study, an online examination information system was obtained at universities. The questions are presented in a multiple choice system. The implementation of this online exam system is made with facilities including exam management, exam management, user data management, and taking exams which will produce value output.